The Effect of Project Based Learning Model on Science Learning Outcomes for Grade 4 Elementary School: Pengaruh Model Project Based Learning Terhadap Hasil Belajar IPA Kelas 4 Sekolah Dasar - Isya Nafik; Nur Efendi (Academia Open, 2022)
This experimental quantitative study investigates the impact of the Project Based Learning (PBL) model on science learning outcomes among fourth-grade students at SD Muhammadiyah 2 Krian. The research addresses the lack of innovation by educators in learning implementation, resulting in limited student engagement and poor learning outcomes. The study follows a Nonequivalent Control Group Design, with class 4 Al - Aziz (20 students) as the control group and class 4 Al - Jabbar (20 students) as the experimental group. Cognitive abilities and learning outcomes were measured using a test, and data analysis was conducted using the t-test. The results, obtained through the t-test Paired Sample T Test in SPSS v.24, revealed a significant effect of the Project Based Learning model on the learning outcomes of fourth-grade science students at SD Muhammadiyah 2 Krian (p < 0.05, sig. 2-Tailed = 0.000). This finding supports the rejection of the null hypothesis (H0) and acceptance of the alternative hypothesis (H1). The implication of this research suggests that implementing the Project Based Learning model can enhance science learning outcomes for fourth-grade students, thereby addressing the issue of limited student involvement in learning activities. Highlights: Project Based Learning improves science learning outcomes: The research demonstrates that implementing the Project Based Learning model positively impacts the learning outcomes of fourth-grade students in science. Addressing the lack of student engagement in learning: The study emphasizes the importance of addressing the issue of low student involvement in learning activities by introducing innovative approaches such as Project Based Learning. Experimental study design: The research follows a Nonequivalent Control Group Design, allowing for a comparison between the control group and the experimental group to evaluate the effectiveness of the Project Based Learning model. Keywords: Project Based Learning, Science Learning Outcomes, Fourth Grade, Student Engagement, Experimental Study